Sosialisasi Pencegahan dan Penyalahgunaan Napza Pada Siswa Di SMP Negeri 1 Dolok Silau - Sinuraya, Janwar Frihasan; Barus, Julius Boy Nesra Basgimata; Ginting, Lovellita Br; Sinurat, Hasiholanta S; Ginting, Gama Chrisindo (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
The aim of the socialization service on drug prevention and abuse in Junior High Schools (SMP) at SMP Negeri 1 Dolok Silau is to provide knowledge so that students can understand the impacts resulting from drug use and abuse which include physical, psychological or socio-economic impacts. The socialization activity on drug prevention and abuse was carried out on June 12 2024 with a total of 28 students and class VIII teachers at SMP Negeri 1 Dolok Silau, North Sumatra Province. Therefore, through prevention and abuse outreach activities, students at SMP Negeri 1 Dolok Silau provide understanding and increased knowledge about the types of narcotics, the negative impacts of drugs such as from physical, psychological, educational, social and economic aspects as well as ways to prevent and overcome abuse. drugs among children and adolescents. For this reason, this outreach activity can protect the younger generation as the nation's next generation, especially students at SMP Negeri 1 Dolok Silau from the dangers of drug abuse and provide tips for students to prevent and stay away from drugs, both in the school environment and in the surrounding environment.